PENGARUH STRATEGI BISNIS DAN KEUNGGULAN BERSAING TERHADAP KINERJA PEMASARAN PADA USAHA KECIL MENENGAH SONGKOK “UDENG BALI” GENTENG BANYUWANGI - Ach Hasan Hasyim (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
The tight competition in the business world, makes SMEs must have a business strategy and competitive advantage, both in knowledge and enterpeneurship ability, the creation of a sustained competitive advantage will create superior marketing performance acceptable to consumers. This study examines the influence of business strategy and competitive advantage on the marketing performance of MSMEs songkok